Nursing relevance, according to the competencies perceived by the graduates of the Guayaquil University - Dinora Rebolledo Malpica; Carmen Alexandra Sánchez Hernández; Gloria Muñiz Granoble; María Araceli García Martínez; Miriam Muñoz Aucapiña; Betzaida Salomet Cerezo Leal (Medisur)
Foundation: the relevance in health is related to the existing coherence in an intervention project according to the needs of its beneficiaries; In this it is very important that the professional has the faculties to combine his capacities in the achievement of a certain purpose. Objective: to determine employability indicators according to the competencies in graduates of the Guayaquil University nursing career. Methods: descriptive/explanatory study with a representative sample of 136 graduates of the last five years, to whom an instrument validated by expert judgment (0.89: Cronbach's alpha) was applied. 17 indicators of internal employability and six of external employability were measured. Results: Nursing graduates perceive employability as attributes and competencies of being, with problem-solving skills, being reflective, critical thinking, ethical behaviors, and effective leadership. In relation to external employability, graduates were considered to have attribute competencies that make them competitive in the nursing work environment. Conclusions: Nursing graduates from the Guayaquil University have the attributes and competencies of internal and external employability in accordance with the expectations of the objectives and the nursing professional’s profiles.